Chronic Stress Modulates Microglial Activation Dynamics, Shaping Priming Responses to Subsequent Stress - Junyu Chen; Jiacheng Huang; Taolei Han; Nobuhiko Kojima (Brain Sciences)
(1) Background: The high recurrence rate and individual differences in stress susceptibility contribute to the diverse symptoms of depression, making full recovery and relapse prevention challenging. Emerging evidence suggests that fluctuations in microglial activity are closely linked to depression progression under chronic stress exposure. Changes in the brain microenvironment can elicit microglial priming, enhancing their sensitivity to external stimuli. However, few studies have longitudinally examined how microglial characteristics evolve throughout depression progression. (2) Methods: In this study, we investigated microglial morphological changes and their responses to acute stress at different stages of depression using the chronic unpredictable mild stress (CUMS) paradigm in mice. (3) Results: Our findings reveal that in the dentate gyrus, microglial activation indices, including cell number and morphology, exhibit distinct dynamic patterns depending on CUMS exposure duration. Notably, after 2 and 4 weeks of CUMS exposure followed by acute stress re-exposure, microglia display opposing response patterns. In contrast, after 6 weeks of CUMS exposure, primed microglia exhibit dysfunction, failing to respond to acute stress. Notably, depressive behaviors are not prominent after 2 weeks of CUMS exposure but become more pronounced after 4 and 6 weeks of exposure. Additionally, regardless of CUMS duration, body weight demonstrates an intrinsic capacity to normalize after stress cessation. (4) Conclusions: These findings suggest that microglial priming responses are state-dependent, either enhancing or suppressing secondary stimulus responses, or exceeding physiological limits, thereby preventing further activation. This study provides novel insights into the role of microglial priming in stress vulnerability and its contribution to depression progression.